2016
DOI: 10.1038/ni.3563
|View full text |Cite
|
Sign up to set email alerts
|

Protective neutralizing influenza antibody response in the absence of T follicular helper cells

Abstract: Virus infection induces the development of T follicular helper (T) and T helper 1 (T1) cells. Although T cells are important in anti-viral humoral immunity, the contribution of T1 cells to a protective antibody response remains unknown. We found that IgG2 antibodies predominated in the response to vaccination with inactivated influenza A virus (IAV) and were responsible for protective immunity to lethal challenge with pathogenic H5N1 and pandemic H1N1 IAV strains, even in mice that lacked T cells and germinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 55 publications
6
141
3
Order By: Relevance
“…Interestingly, these mice expressed elevated levels of IgG2a antibodies suggesting a dominant role for IFN‐γ in the absence of IL‐4 signalling and no requirement for prior IgG1 expression . Similarly, it has been recently shown that Bcl6 mutant mice despite the absence of Tfh cells (therefore no IL‐4) can produce significant amounts of anti‐viral IgG2 driven by IFN‐γ + Th1 (CXCR3 + CXCR5 − ) and IFN‐γ + Tfh‐like (CXCR3 + CXCR5 + ) cells in B‐cell follicles .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, these mice expressed elevated levels of IgG2a antibodies suggesting a dominant role for IFN‐γ in the absence of IL‐4 signalling and no requirement for prior IgG1 expression . Similarly, it has been recently shown that Bcl6 mutant mice despite the absence of Tfh cells (therefore no IL‐4) can produce significant amounts of anti‐viral IgG2 driven by IFN‐γ + Th1 (CXCR3 + CXCR5 − ) and IFN‐γ + Tfh‐like (CXCR3 + CXCR5 + ) cells in B‐cell follicles .…”
Section: Discussionmentioning
confidence: 92%
“…IL‐4 expressed by Tfh cells activates B cell STAT6 responsive germline transcription, resulting in, VDJ recombination and expression of IgG1 or IgE isotypes . Tfh cells expressing interferon‐γ (IFN‐γ) are derived from the Th1 lineage and are thought to be required for B cell CSR and IgG2a/c expression, providing protective immunity to infection . In mice, during T‐cell independent B‐cell stimulation, IFN‐γ or IL‐27 is thought to activate STAT1/T‐bet/Ets‐1 responsive germline transcription and IgG2a CSR .…”
Section: Introductionmentioning
confidence: 99%
“…IFNγ production by Tfh cells is dependent on STAT4 signaling, which presumably leads to T-bet-dependent and -independent chromatin remodeling at the Ifng locus to retain accessibility even after T-bet expression is lost 99,100. In type 1 infection settings such as influenza and Plasmodium chabaudi, a population of IFNγ and IL-21 double producing T cells confer protection in part through facilitating humoral immunity yet are able to retain their cytokine production profile even in the absence of Bcl6 101,102. Despite the suggested importance of IFNγ and IL-21 double producers, it remains unclear how these cells are functionally distinct from IFNγ and IL-21 single producers, as are the potentially different effects of the same cytokine(s) delivered by Th1 cells and Tfh cells.…”
mentioning
confidence: 99%
“…The Ab response to infection varies depending on the types of infectious pathogens (12,19,20). Although B cells and IgG Abs are critical for protection against C. rodentium (9), it is not clear which IgG subclasses are involved.…”
Section: Resultsmentioning
confidence: 99%
“…During this process, the isotypes of the Ab responses are pathogen dependent and differ from those elicited by the Ags. IgG2 are known as effective virus-neutralizing Abs that provide protective responses (12,19). Recent research indicates that IgG1, but not IgG2a, is required in immune protection against Salmonella typhimurium (20).…”
Section: Discussionmentioning
confidence: 99%